2005
DOI: 10.1016/j.cogbrainres.2005.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Optic flow dominates visual scene polarity in causing adaptive modification of locomotor trajectory

Abstract: Locomotion and posture are influenced and controlled by vestibular, visual and somatosensory information. Optic flow and scene polarity are two characteristics of a visual scene that have been identified as being critical in how they affect perceived body orientation and self-motion. The goal of this study was to determine the role of optic flow and visual scene polarity on adaptive modification in locomotor trajectory. Two computer-generated virtual reality scenes were shown to subjects during 20 minutes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…The crucial role of visual demand for ARD could be related to the fact that already single-task walking requires substantial visual processing, since we need to navigate through visually defined space [10][11][12]. Thus, ARD seem to reflect seniors' problems to concurrently process two streams of visuo-spatial information, one related to walking and the other to a visual non-walking task.…”
Section: Introductionmentioning
confidence: 89%
“…The crucial role of visual demand for ARD could be related to the fact that already single-task walking requires substantial visual processing, since we need to navigate through visually defined space [10][11][12]. Thus, ARD seem to reflect seniors' problems to concurrently process two streams of visuo-spatial information, one related to walking and the other to a visual non-walking task.…”
Section: Introductionmentioning
confidence: 89%
“…Human ability to adjust gait patterns has been explored with manipulations of optic flow, body loading, and the support surface, and each modality has been successful in inducing adaptive locomotor changes [1][2][3][4][5][6][7][8][9]. Subjects who walked on a treadmill while viewing immersive, rotating visual scenes showed adaptive changes both during their exposure and during post-exposure testing [5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects who walked on a treadmill while viewing immersive, rotating visual scenes showed adaptive changes both during their exposure and during post-exposure testing [5,6,8]. Prokop et al showed that optic flow modulates a selfselected walking velocity and suggested that an individual's strategy to stabilize walking velocity depends on the way information is weighted from different afferent sources [7].…”
Section: Introductionmentioning
confidence: 99%
“…With increasing age, individuals seem to rely more on exteroceptive information and prioritize the use of vision to control the balance (4), so a de icit would directly affect the movement, since the stability and body position are constantly adjusted by optical low and positioning cues (5).…”
Section: Introductionmentioning
confidence: 99%